Practice patterns and perceptions of Australian and New Zealand anaesthetists towards perioperative oxygen therapy. Issue 3 (May 2019) - Frei, Daniel R; Beasley, Richard; Campbell, Douglas; Leslie, Kate; Merry, Alan F; Moore, Matthew; Myles, Paul S; Ruawai-Hamilton, Laura; Short, Tim G; Young, Paul J
We conducted a survey of Australian and New Zealand anaesthetists to determine self-reported practice of perioperative oxygen administration and to quantify perceptions regarding the perceived benefits and risks resulting from liberal oxygen therapy delivered in a manner consistent with the current World Health Organization guidelines. In addition, we sought feedback on the acceptability of several proposed clinical trial designs aiming to assess the overall effect of liberal and restricted perioperative oxygen regimens on patient outcomes. We developed a 23-question electronic survey that was emailed to 972 randomly selected Australian and New Zealand College of Anaesthetists (ANZCA) Fellows. We received responses from 282 of 972 invitees (response rate 29%). The majority of survey participants indicated that they routinely titrate inspired oxygen to a level they feel is safe (164/282, 58%) or minimise oxygen administration (82/282, 29%), while 5% of respondents indicated that they aim to maximise oxygen administration. The mean value for targeted intraoperative fraction inspired oxygen (FiO2 ) was 0.41 (standard deviation 0.12). Of the survey respondents, 2/282 (0.7%) indicated they believe that routine intra- and postoperative administration of ≥80% oxygen reduces the risk of surgical site infection. Well-designed and conducted randomised trials on this topic may help to better direct clinicians' choices. A high level of willingness to participate (80% of responses) in a study designed to investigate the impact of differing approaches to perioperative oxygen administration suggests that recruitment is likely to be feasible in a future study.